An Oncogenic Role for Four-Jointed Box 1 (FJX1) in Nasopharyngeal Carcinoma. (19th May 2019) - Chai, San Jiun; Ahmad Zabidi, Muhammad Mamduh; Gan, Siew Pey; Rajadurai, Pathmanathan; Lim, Paul Vey Hong; Ng, Ching Ching; Yap, Lee Fah; Teo, Soo Hwang; Lim, Kue Peng; Patel, Vyomesh; Cheong, Sok Ching
Abstract : Nasopharyngeal carcinoma (NPC) is a highly metastatic cancer prevalent in Southern China and Southeast Asia. The current knowledge on the molecular pathogenesis of NPC is still inadequate to improve disease management. Using gene expression microarrays, we have identified the four-jointed box 1 ( FJX1 ) gene to be upregulated in primary NPC tissues relative to nonmalignant tissues. An orthologue of human FJX1, the four-jointed (fj) gene in Drosophila and Fjx1 in mouse, has reported to be associated with cancer progression pathways. However, the exact function of FJX1 in human is not well characterized. The overexpression of FJX1 mRNA was validated in primary NPC tissue samples, and the level of FJX1 protein was significantly higher in a subset of NPC tissues (42%) compared to the normal epithelium, where no expression of FJX1 was observed (p = 0.01 ). FJX1 is also found to be overexpressed in microarray datasets and TCGA datasets of other cancers including head and neck cancer, colorectal, and ovarian cancer. Both siRNA knockdown and overexpression experiments in NPC cell lines showed that FJX1 promotes cell proliferation, anchorage-dependent growth, and cellular invasion. Cyclin D1 and E1 mRNA levels were increased following FJX1 expression indicating that FJX1 enhances proliferation by regulating key proteins governing the cell cycle. Our data suggest that the overexpression of FJX1 contributes to a more aggressive phenotype of NPC cells and further investigations into FJX1 as a potential therapeutic target for NPC are warranted. The evaluation of FJX1 as an immunotherapy target for NPC and other cancers is currently ongoing.